Analysis of the type material of Gomphosphenia tackei (Bacillariophyceae) and comparison to epizoic diatom populations on freshwater snails - Mateusz Rybak; Łukasz Peszek; Anita Poradowska (Plant Ecology and Evolution, 2021)
Background and aims – Hustedt (1942) originally described Gomphosphenia tackei from Germany under the name Gomphonema tackei. Because of the small cell size and the lack of scanning electron microscopy (SEM) images from the type material, it is often confused with other species from this genus, especially with G. stoermeri. The aim of this paper was to present detailed morphological characteristics of G. tackei based on the analysis of the type material and of several epizoic populations from Central Europe. Material and methods – The material in this study was collected from the shells of the freshwater snails Lymnaea stagnalis, Planorbarius corneus, and Planorbis planorbis. Additionally, for an unambiguous species identification, the type material for Gomphosphenia tackei was analyzed using light and scanning electron microscopes.Key results – The presence of Gomphosphenia tackei was confirmed in the studied material. The largest population (up to 19%) was recorded on the shell surfaces of living snails, whereas on empty shells, the diatom did not seem to be present or only in very low numbers. Valves are typically clavate with rounded apices. Valves are frequently observed in girdle view, often joint together in pairs. The valves in the studied populations had a valve length of 7–29 µm, a valve width of 3–4 µm, and a stria density of 25–29 striae in 10 µm. In the type population, valve length ranged from 7.5 to 27 µm with a valve width of 3.0–4.0 µm and a stria density of 23–29 striae per 10 µm. Striae were composed of 2–4 elongated to rounded areolae per stria. At the apices, the striae were composed of one single areola. The cells were attached to the substratum by their footpole.Conclusion – Published illustrations of Gomphosphenia tackei do not always correctly represent this species. Individual cells are attached to the substratum by secreted mucilage, probably via their areolae or girdle band pores located on the footpole.